Knowledge Management and Performance: Unveiling Creativity’s Role in Higher Education for Sustainable Development - Fahadha, Rizqa Ula; Maarif, Muhammad Syamsul; Yulianto, Budi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study investigates the impact of knowledge management on team member performance, with a focus on the mediating role of team member creativity, within the context of higher education institutions as strategic contributors to sustainable economic development.Method: This research adopts a quantitative explanatory approach, utilizing a survey methodology that includes 100 respondents, comprising lecturers and educational staff from a university located in Central Java, Indonesia. Data were gathered through a closed-ended Likert scale questionnaire and analyzed employing the Structural Equation Modeling Partial Least Squares (SEM-PLS) method, facilitated by SmartPLS software.Result: The findings of the study reveal that knowledge management exerts a positive and significant influence on team member performance, both directly and indirectly through team member creativity as a mediating variable. Furthermore, team member creativity has been identified as a critical factor in enhancing the relationship between knowledge management and individual performance.Practical Implications for Economic Growth and Development: These results provide substantial practical implications, indicating that the implementation of effective knowledge management practices can cultivate a creative, innovative, and productive organizational culture, thereby contributing to knowledge-based economic growth within the higher education sector. This research contributes theoretically by deepening the understanding of creativity as a cognitive mechanism within the Knowledge-Based View framework, while also offering practical insights for institutional leaders to develop policies aimed at enhancing human resource capabilities.Originality/Value: This study presents an integrative model that explores the mediating role of psychological variables within a theoretical framework pertinent to the reinforcement of knowledge-based organizations in the higher education sector.